AtPR5K2, a PR5-Like Receptor Kinase, Modulates Plant Responses to Drought Stress by Phosphorylating Protein Phosphatase 2Cs - Baek, Dongwon; Kim, Min Chul; Kumar, Dhinesh; Park, Bokyung; Cheong, Mi Sun; Choi, Wonkyun; Park, Hyeong Cheol; Chun, Hyun Jin; Park, Hee Jin; Lee, Sang Yeol; Bressan, Ray A.; Kim, Jae-Yean; et al. (Frontiers in Plant Science, 2019)
Cell surface receptors perceive signals from the environment and transfer them to the interior of the cell. The Arabidopsis thaliana PR5 receptor-like kinase (AtPR5K) subfamily consists of three members with extracellular domains that share sequence similarity with the PR5 proteins. In this study, we characterized the role of AtPR5K2 in plant drought-stress signaling. AtPR5K2 is predominantly expressed in leaves and localized to the plasma membrane. The atpr5k2-1 mutant showed tolerance to dehydration stress, while AtPR5K2-overexpressing plants was hypersensitive to drought. Bimolecular fluorescence complementation assays showed that AtPR5K2 physically interacted with the type 2C protein phosphatases ABA-INSENSITIVE 1 (ABI1) and ABI2 and the SNF1-related protein kinase 2 (SnRK2.6) proteins, all of which are involved in the initiation of abscisic acid (ABA) signaling; however, these interactions were inhibited by treatments of exogenous ABA. Moreover, AtPR5K2 was found to phosphorylate ABI1 and ABI2, but not SnRK2.6. Taken together, these results suggest that AtPR5K2 participates in ABA-dependent drought-stress signaling through the phosphorylation of ABI1 and ABI2.